European development NGOs and the diversion of aid: Contestation, fence‐sitting, or adaptation?. (17th October 2019) - Rozbicka, Patrycja; Szent‐Iványi, Balázs
Abstract: Motivation: The article examines the advocacy strategies of European non‐government development organizations (NGDOs). The development aid literature has not put much emphasis on understanding NGDOs' aid‐related advocacy strategies, and the literature on interest groups has so far neglected to explain why groups select different advocacy strategies within the same policy area. Purpose: The article explains how NGDOs have selected advocacy strategies during the process of reformulating the European Consensus in 2016/17, in response to attempts by the European Union (EU) to divert aid from poverty reduction to three other goals: managing migration, funding climate change adaptation (CCA), and funding the private sector. Approach and methods: The article develops a framework explaining NGDOs' strategy selection, looking at the politicization of the policy change, its impact on NGDOs' funding, and its relation to the groups' normative positions. The article uses qualitative data from NGDO documents and interviews with senior staff of NGDO networks based in Brussels. Findings: NGDOs used different strategies for the three cases of aid diversion: they contested aid diversion for managing migration; mainly choose fence‐sitting in case of CCA; and gradually became more adaptive towards diverting aid to fund the private sector. The three variables of politicization, impact on funding, and relation to normative positions explain the strategies selected by NGDOs in all three cases. Policy implications: The findings can help NGDOs in selecting the most appropriate advocacy strategies for changes in aid policy, allowing them to become more effective in influencing the EU institutions and member state governments.